2016
DOI: 10.1097/iae.0000000000001103
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Uveitis, Different Types of Viral Hepatitis, and Liver Cirrhosis

Abstract: Viral hepatitis may increase the risk of subsequent uveitis. Patients with hepatitis B virus and hepatitis C virus coinfection had the highest risk. Patients with cirrhosis had a higher risk in the multivariable model but did not attach statistic difference. Although these epidemiologic studies yielded informative results, the underlying mechanism remains to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The association between viral hepatitis and uveitis has been proposed in a few studies, most of which investigated the role of hepatitis B and C in the pathogenesis of uveitis. These studies noted that deposition of circulating immune complexes, physiologic immune reaction against an infection within the eye, and complement-mediated immune activation may lead to extra-hepatic manifestations such as glomerulonephritis, uveitis, and polyarteritis nodosa [ 3 5 ]. Tien at el.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between viral hepatitis and uveitis has been proposed in a few studies, most of which investigated the role of hepatitis B and C in the pathogenesis of uveitis. These studies noted that deposition of circulating immune complexes, physiologic immune reaction against an infection within the eye, and complement-mediated immune activation may lead to extra-hepatic manifestations such as glomerulonephritis, uveitis, and polyarteritis nodosa [ 3 5 ]. Tien at el.…”
Section: Discussionmentioning
confidence: 99%
“…in a cohort study on the relationship between uveitis and the different types of viral hepatitis concluded that patients with hepatitis B virus and HCV co-infection have the highest risk of uveitis. Also, They reported only one case of uveitis among 82 cases of isolated HAV infection (rate:19.44 per 10,000 person-years) [ 5 ]. The extra-hepatic manifestations which reported to be associated with HAV infection include glomerulonephritis, acute renal failure (ARF), myositis, acute pancreatitis, arthritis, pleural or pericardial effusion, myocarditis, autoimmune thrombocytopenic purpura, erythematous maculopapular rash, and parotitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Uveitis is a rare complication of acute viral hepatitis B and C which has not been reported as a presentation or extra-hepatic manifestation of hepatitis A virus (HAV) infection so far. (3,4,5) Hepatitis A is a self-limited viral infection with an average 30 days (range 15 to 49 days) of incubation period. (6) In this case study we report a rare case of bilateral granulomatous AU as an extra-hepatic manifestation of HAV infection in an immunocompetent patient.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the virus may infect lymphatic cells or induce chronic low-grade inflammation that secondarily influences DR, the pathogenesis of which is known to include a prominent inflammatory component. The potential contribution of HCV to inflammatory ocular disease is highlighted by a recent study suggesting higher rates of uveitis among patients with HCV infection 9…”
Section: Introductionmentioning
confidence: 99%